Growth of Trichomycterus punctulatus “Life” in three population densities in intensive culture system with recirculation - López Cubas, Segundo Juan (2013)
The present research was conducted in order to determine the effect of population density on the growth of Trichomycterus punctulatus, in an intensive culture system with recirculation, to which was applied Increasing Stimulus Experimental Design with three treatments without repetition: 2.21 lifes / liter, 2.94 lifes / liter and 3.68 lifes / liter. The fish were fed a diet of 32% protein and were sampled monthly growth as well as physical and chemical parameters of the water. We applied ANOVA and Duncan test. Growth of T. punctulatus was affected by population density in direct, with a higher density of 3.68 lifes / liter: 90.90 mm and 5.95 g; also the overall production per cubic meter and observed the same trend. The physicochemical parameters of the water were similar among treatments and were within the ranges of good development for fish.